Application of Ling Tien Kung Movement Technique in Reducing Diabetes Mellitus in Elderly - Nyna Puspita Ningrum; Retno Setyo Iswati; Indria Nuraini (Universitas STRADA Indonesia, 2019)
Diabetes Mellitus (DM) in the elderly is a disease with blood glucose levels increasing from the normal value affected by the insulin hormone. As the age increases, the risk of DM increases, due to a decrease in physiology and biochemistry in the body's system. Therapy or solutions that can be done to overcome diabetes in the elderly can be done pharmacological or non-pharmacological. One of the non-pharmacological therapies is by doing the Ling Tien Kung movement. The Ling Ting Kung movement is a therapy centered on anal training,